Divergence of Ant Communities Over Time in a Fragmented Atlantic Rain Forest Landscape - Soares Ribeiro, Vanessa Soares Ribeiro; Navarro Paolucci, Lucas; Schoereder, José Henrique; Ribeiro de Castro Solar, Ricardo (Sociobiology, 2022)
Habitat fragmentation changes biological communities and its spatiotemporal dynamics – which may lead to either biotic homogenization or heterogenization along time and space. Both processes can occur by addition, replacement or loss of species within communities, altering compositional similarity across the landscape. We investigated which of these two processes (biotic homogenization or heterogenization) occurs, and its possible underlying mechanism, over 15 years in an Atlantic Forest landscape using ants as model organisms. We sampled ants in 17 forest fragments across three different years, compared their composition similarity, species richness, and species richness of groups classified according to their habitat preferences. We sampled a total of 132 ant species. Ant communities in fragments diverged over time, suggesting they experienced an idiosyncratic structuring process. This biotic heterogenization occurred through an additive process, as ant species richness increased over time, mainly due to an increase of generalist ant species, and a decrease of forest specialist ant species. These changes occurred despite the higher forest cover in the landscape along years. Since different species can perform different functions in ecosystems, this biotic heterogenization may have implications for ecosystem functioning. Investigating how disturbances structure biological communities over time, especially those performing important ecosystem functions, can shed light to our understanding of possible changes in ecosystem functions and consequently for forest regeneration.